M. K. Kadyrbaev’s Archive as a Source for Studying the Stone Monuments of Kazakhstan - Lyubov N. Ermolenko; Asemgul D. Kasenova; Zholdasbek K. Kurmankulov (СибСкрипт, 2023)
The article describes the unpublished archives collected by M. K. Kadyrbaev from his field work in Central Kazakhstan in 1955–1979. It provides information on eight stone statues and structures. The authors attributed and dated them in line with the contemporary rules of archeology. One of the statues appeared to belong to the Saka period of the Tasmola culture. Another monument had no obvious analogies but, possibly, was part of a Qipcaq sanctuary. The authors also touched upon some challenging or debatable issues raised by M. K. Kadyrbaev and other expedition members, e.g., the validity of correlating statues without sings of sex with images of women; the secret Polovtsian sanctuary, which have to be studied in the context of similar Qipcaq sites, etc.